The South Pole Telescope bolometer array and the measurement of secondary Cosmic Microwave Background anisotropy at small angular scales - Shirokoff, Erik D. (eScholarship, University of California, 2011)
The South Pole Telescope (SPT) is a dedicated 10-meter diameter telescope optimized for mm-wavelength surveys of the Cosmic Microwave Background (CMB) with arcminute resolution. The first instrument deployed at SPT features a 960 element array of horn-coupled bolometers. These devices consist of fully lithographed spider-web absorbers and aluminum-titanium bilayer transition edge sensors fabricated on adhesive-bonded silicon wafers with embedded metal backplanes. The focal plane is cooled using a closed cycle pulse-tube refrigerator, and read-out using Frequency Domain Multiplexed Superconducting Quantum Interference Devices (SQUIDs.) Design features were chosen to optimize sensitivy in the atmospheric observing bands available from the ground, and for stability with the frequency domain multiplexed readout system employed at SPT, and performance was verified with a combination of laboratory tests and field observations. In 2008 the SPT surveyed 200 square-degrees at 150 and 220 GHz. These data have been analyzed using a cross-spectrum analysis and multi-band Markov Chain Monte Carlo parameter fitting using a model that includes lensed primary CMB anisotropy, secondary thermal (tSZ) and kinetic (kSZ) Sunyaev-Zel'dovich anisotropies, unclustered synchrotron point sources, and clustered dusty point sources. In addition to measuring the power spectrum of dusty galaxies at high signal-to-noise, the data primarily constrain a linear combination of the kSZ and tSZ anisotropy contributions (at 150 GHz and ell=3000): DtSZ3000 + 0.5 DkSZ3000 = 4.5 ± 1.0 &mu K2, and place the lowest limits yet measured on secondary anisotropy power.